24-hour changes in ACTH, corticosterone, growth hormone, and leptin levels in young male rats subjected to calorie restriction - Chacón, Fernando (2005)
Calorie restriction of young male rats increases plasma prolactin, decreases luteinizing hormone (LH) and testosterone, and disrupts their 24 h secretory pattern. To study whether this could be the consequence of stress, we examined the 24 h variations of plasma adrenocorticotropic hormone (ACTH) corticosterone, growth hormone (GH), leptin, and adrenal corticosterone. Rats were submitted to a calorie restriction equivalent to a 66% of usual intake for 4 weeks, starting on day 35 of life. Controls were kept in individual cages and allowed to eat a normal calorie regimen. Significantly lower ACTH levels were detected in calorie‐restricted rats. Plasma corticosterone levels during the light phase of the daily cycle were significantly higher in calorie‐restricted rats. Time‐of‐day variation in plasma ACTH and corticosterone levels attained significance in calorie‐restricted rats only, with a maximum toward the end of the resting phase. The daily pattern of adrenal gland corticosterone mirrored that of circulating corticosterone; however, calorie restriction reduced its levels. Plasma ACTH and corticosterone correlated significantly in controls only. Calorie restriction decreased plasma GH and leptin, and it distorted 24 h rhythmicity. In a second study, plasma ACTH and corticosterone levels were measured in group‐caged rats, isolated control rats, and calorie‐restricted rats during the light phase of the daily cycle. Plasma ACTH of calorie‐restricted rats was lower, and plasma corticosterone was higher, compared with isolated or group‐caged controls. The changes in the secretory pattern of hormones hereby reported may be part of the neuroendocrine and metabolic mechanisms evolved to maximize survival during periods of food shortage.